Combination of Pumpkin Flour (Cucurbita moschata D.) and Carrot Flour (Daucus carota L.) on The Brightness Color of Koi Fish (Cyprinus carpio) - M. Riswan Maulana; Muhammad Junaidi; Bagus Dwi Hari Setyono (Jurnal Biologi Tropis, 2021)
Koi fish is one of the freshwater ornamental fish that has an attractive body color, so the color disorder needs attention. The natural feed for pumpkin flour combined with carrot flour in artificial feed aims to improve the color quality of the koi fish. The study used a completely randomized design design (CRD) with 5 treatments and 3 replications so that 15 experimental units were obtained, each experimental unit contained 10 koi fish, and there were 5 treatments; P0 100% Pellets, P1 contains 90% Pellets + 3% LK Flour + TW 7%, P2 contains 90% Pellets + 4% LK Flour + 6% W Flour, P3 contains 90% Pellets + 5% LK Flour + W 5 Flour %, P4 contains 90% Pellets + 6% LK Flour + 4% W Flour. In this study, the highest increase in color value in koi fish occurred in the P4 treatment with the addition of a combination of 6% pumpkin flour and 4% carrot flour. The parameters in the study were the increase in color quality, increase in length and weight of koi fish, SR, and water quality. Observation data were analyzed using analysis of variance (AN0VA).